Observational Evidence of Generation and Propagation of Barotropic Rossby Waves Induced by Tropical Instability Waves in the Northeastern Pacific - Kang‐Nyeong Lee; Chanhyung Jeon; YoungHo Seung; Hong‐Ryeol Shin; Seung‐Kyu Son; Jae‐Hun Park (Geophysical Research Letters)
Abstract Tropical instability waves (TIWs) in the equatorial eastern Pacific exhibit 25–40‐day westward‐propagating fluctuations with seasonal and interannual variations, which are stronger during July–December and La Niña periods. There is evidence that the instability of the equatorial currents that generates TIWs also induce radiation of barotropic Rossby waves (BTRWTIW). Long‐term near‐bottom current measurements at 10.5°N and 131.3°W during 2004–2013 revealed a spectral peak at 25–40 days, where significant coherences were found with satellite‐measured sea surface height with maxima approximately 5°N. Simulated deep currents from a data‐assimilated ocean model concur with the observed near‐bottom currents, and both currents vary seasonally and interannually, consistent with the typical characteristics of TIW. Further analyses using 25–40‐day bandpass‐filtered barotropic velocity data from the model revealed that they reasonably satisfied the theoretical dispersion relation of BTRWTIW. The in situ and model analysis support the conclusion that BTRWTIW propagate north of 10°N in the northeastern Pacific.